2023
DOI: 10.20452/pamw.16604
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer in diagnosis and prevention of venous thrombosis: recent advances and their practical implications

Benilde Cosmi,
Cristina Legnani,
Alessia Libra
et al.

Abstract: D -Dimers and venous thromboembolism 1 extent of fibrinolysis, and clearance of fibrin degradation products.D -Dimer level increases physiologically with age and during pregnancy and puerperium; it may be higher in African -Americans and in smokers. Increased D -dimer level is also observed in several pathologic conditions, in which stabilized fibrin is formed and subsequently degraded, such as in venous and arterial thrombosis, infectious diseases, neoplasms, trauma, surgery, liver disease, renal insufficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…D-dimer level is well-established independent risk factor of thromboembolism recurrence and is incorporated in several prediction models; however the presence of antiphospholipid antibodies and elevated D-dimer represent rather independent risk factors. 37,38 Interestingly, the difference was driven by patients on apixaban, since no such association was seen in the VKA group. It might be speculated that D-dimer measurement might help identify patients with APS in whom VKA therapy should be strongly recommended and apixaban is a much less likely effective option, but this practical implication requires further study.…”
Section: Discussionmentioning
confidence: 97%
“…D-dimer level is well-established independent risk factor of thromboembolism recurrence and is incorporated in several prediction models; however the presence of antiphospholipid antibodies and elevated D-dimer represent rather independent risk factors. 37,38 Interestingly, the difference was driven by patients on apixaban, since no such association was seen in the VKA group. It might be speculated that D-dimer measurement might help identify patients with APS in whom VKA therapy should be strongly recommended and apixaban is a much less likely effective option, but this practical implication requires further study.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, patients with primary myelofibrosis who have the same mutation have a significantly longer overall survival rate compared to subjects positive for other mutations (JAK2, V617F, or MPL). Clinically, patients with essential thrombocythemia who are positive for CALR mutations exhibit a lower incidence of thrombotic events [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that TF-EVs promote thrombosis in PDAC patients, while baseline TF levels at the start point of chemotherapy constitute a predictive factor of cancer-related thromboembolism, as was demonstrated in Japanese PDAC patient cohorts [ 154 ]. It was also demonstrated in the study of Kobayashi et al (2021) that TF levels above or equal to 100 pg/Ml constitute an independent predictive factor for cancer-associated thromboembolism, while it was also proposed that D-dimers and microvesicle tissue factor (MV-TF) could be utilized as biomarkers for venous thromboembolism in PDAC and may facilitate the identification of patients for whom thromboprophylaxis has to be administrated [ 154 , 155 ].…”
Section: The Effects Of Evs In Pdac-associated Thrombosismentioning
confidence: 99%